Community Adaptation Factors in Tanjunguban-Telaga Punggur Crossingthe North Wind Season in Riau Island - Suci Maharani (Science and Environmental Journal for Postgraduate, 2021)
This research is motivated to find out the community adaptation in Tanjunguban-Telaga Punggur Crossing During the North Wind Season in Riau Island. Research location at Tanjunguban-Telaga Punggur Crossing. This study uses a qualitative approach with the type of descriptive research. Primary data collection in this study uses interviewing, observation and documentation techniques, while secondary data is collected by searching literature books and searching internet media. The selection of informants is done by purposive sampling. The results of the study carried out that (1) Community factor continue to cross the north wind namely; a. the north wind season coincides with school holidays, b. the north wind season coincides with Christmas and New Year, c. the north monsoon coincides with Chinese New Year. (2) The strategies adopted include: a) crossing before 10:00 WIB, b) changing lanes or access roads, c) choosing to use transportation that is considered safer.